ON BEING THEOLOGICALLY HOSPITABLE TO JESUS CHRIST: HANS FREI'S ACHIEVEMENT - Ford, David (The journal of theological studies, 1995)
DAVID F. FORD; ON BEING THEOLOGICALLY HOSPITABLE TO JESUS CHRIST: HANS FREI'S ACHIEVEMENT, The Journal of Theological Studies, Volume 46, Issue 2, 1 October 199